2004
DOI: 10.1509/jmkr.41.4.479.47015
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Marketing Systems for Complex Products: A Triadic Perspective

Abstract: Products that require extensive and complex information flows among suppliers, intermediary vendors, and customers often pose particular challenges to the vertical marketing system. Using social network theory, the authors investigate buyers' preferences for specific patterns of relationships among buyers, intermediary vendors, and suppliers of complex products. Using a conjoint experiment with actual and prospective buyers of integrated computer networks and services, the authors find that beyond their dyadic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
138
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(146 citation statements)
references
References 26 publications
7
138
0
1
Order By: Relevance
“…Our research proposition suggests that good relationship amongst supply chain members have performance benefits to individual supply chain members as well as the performance of the whole supply chain ( Figure 1). The SNT is therefore relevant to this paper and has been successfully applied in previous triadic supply chain studies (Holma, 2012;Peng, Lin, Martinez, & Yu, 2010;Trienekens, 2011;Wuyts, Stremersch, Van den Bulte, & Franses, 2004). Hence, the application of the social network theory will be useful in advancing conceptual and practical understanding of the performance implications of RQ in a triadic context.…”
Section: Theoretical Perspectives and Hypothesismentioning
confidence: 99%
“…Our research proposition suggests that good relationship amongst supply chain members have performance benefits to individual supply chain members as well as the performance of the whole supply chain ( Figure 1). The SNT is therefore relevant to this paper and has been successfully applied in previous triadic supply chain studies (Holma, 2012;Peng, Lin, Martinez, & Yu, 2010;Trienekens, 2011;Wuyts, Stremersch, Van den Bulte, & Franses, 2004). Hence, the application of the social network theory will be useful in advancing conceptual and practical understanding of the performance implications of RQ in a triadic context.…”
Section: Theoretical Perspectives and Hypothesismentioning
confidence: 99%
“…For mapping out the possible pathways of artisanal dimension stone from the production point to the consumption (building) site, the study relied on the example of Wuyts et al (2004) on vertical marketing systems. Although considering a triadic perspective of vertical marketing systems, Wuyts et al (2004) suggested that multiple analyses are possible for more than three tiers; hence this study adopted a polyadic perspective as shown in Figure 3.…”
Section: Exchange Relationships Within the Marketing Channelsmentioning
confidence: 99%
“…Although considering a triadic perspective of vertical marketing systems, Wuyts et al (2004) suggested that multiple analyses are possible for more than three tiers; hence this study adopted a polyadic perspective as shown in Figure 3. From Figure 3, seven most probable pathways can be identified: Producer 1-the artisanal production unit sells to a developer introduced by a broker and the developer hires transport services to haul the stone to the building site Producer 2-the artisanal production unit sells to a stockist (vendor) who hires transport services to haul the stone to the sale yard for resale to developers Producer 3-the artisanal production unit sells directly to a developer who hires transport services to haul the stone to the building site Producer 4-the artisanal production unit sells to a stockist (vendor) who uses own transport means to haul the stone to the sale yard for resale to developers Producer 5-the artisanal production unit sells to a contractor who hires transport services to haul the stone to the building site Producer 6-the artisanal production unit sells directly to a developer who uses own transport means to haul the stone to the building site Producer 7-the artisanal production unit sells to a contractor who uses own transport means to haul the stone to the building site.…”
Section: Exchange Relationships Within the Marketing Channelsmentioning
confidence: 99%
“…Conversely, existing channel research provides little to no insight into how WOM should affect channel design and management. It is possible that WOM among customers facilitates market learning by channel or supply chain partners, which in turn affects the decision of how to structure the pattern of ties between upstream and downstream companies (Wuyts et al 2004). This would be an example of how marketing strategy can actively shape the interlock of horizontal and vertical networks.…”
Section: New Product Exclusivity / 99mentioning
confidence: 99%